ANALISIS BEBAN KERJA FISIOLOGIS OPERATOR DI STASIUN PENGGORENGAN PADA INDUSTRI KERUPUK - Ernitua Purba; A. Jabbar M. Rambe; Anizar M.kes (Jurnal Teknik Industri USU, 2014)
UD. XYZ is a company that produces crackers. The condition of real floor production found a lot of activity manual one of them is the frying. Physical workload examined in order to determine the energy consumption and % CVL. Based on Standard Nordic Questionnaire (SNQ) that are spread, known that women operators had the highest percentage of very sick category is 47.4%, and male about 28.2%. Measurements for the women showed that 80% of energy consumption carriers are in the weight category is 351-379 Kcal / h while the men only 20% were in the severe category. Based on %CVL operators are in a category of women operators needed repairs and operators of men only 60% who are in the category of necessary repairs the rest are in the category of fatigue does not occur.